Some type of rotational scheme - Nashat Faried; Zeinab Abdel-Kader (International Journal of Mathematics and Mathematical Sciences)
The aim of this paper is to construct a rotational product scheme in the product of Banach spaces with rotational schemes. Besides we give an equivalent definition of the generalized Kolmogorov diameters suggested by Aksoy and Nakamura in 1986, and give the generalized Kolmogorov diameters of the product (∏ i∈n Di) of bounded subsets Di in the product of Banach spaces having schemes in terms of the generalized diameters of Di.